PERAN NEGARA DALAM PENGEMBANGAN BISNIS PT GARUDA INDONESIA: Studi Kasus Kerja Sama PT Garuda Indonesia Dengan Aliansi Global Skyteam Periode 2014 - 2020 - MOIZCA YULYANTI, (2022)
PT Garuda Indonesia is one of the tourism industries which is directly owned by the state. Its existence is very important for the country so that its existence needs to be maintained. PT Garuda Indonesia is trying to improve its performance and with the ambition to defend the title of World Class Airline, in March 2014 PT Garuda Indonesia joined the Global SkyTeam Alliance. This international cooperation is beneficial to see a surge in the number of foreign tourists but the situation has changed since the COVID-19 pandemic hit. It is important for the government as the owner of PT Garuda Indonesia to assist in the business development of PT Garuda Indonesia in this case is its collaboration with the SkyTeam Global Alliance. Keywords: Garuda Indonesia, SkyTeam, International Cooperation, BUMN